2010
DOI: 10.3171/2010.5.peds1032
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal erythropoietin treatment mitigates neural cell loss after systemic prenatal hypoxic-ischemic injury

Abstract: Object Brain injury from preterm birth predisposes children to cerebral palsy, epilepsy, cognitive delay, and behavioral abnormalities. The CNS injury often begins before the early birth, which hinders diagnosis and concurrent treatment. Safe, effective postnatal interventions are urgently needed to minimize these chronic neurological deficits. Erythropoietin (EPO) is a pleiotropic neuroprotective cytokine, but the biological basis of its efficacy in the damaged deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
136
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(155 citation statements)
references
References 60 publications
18
136
1
Order By: Relevance
“…from P1 to P5) normalizes the seizure threshold and motor function in adult rats that suffered prenatal TSHI (Mazur et al, 2010). Here, KCC2 protein expression was quantified at P11 and P28 following prenatal TSHI using the same protocol of postnatal EPO administration.…”
Section: Resultsmentioning
confidence: 99%
“…from P1 to P5) normalizes the seizure threshold and motor function in adult rats that suffered prenatal TSHI (Mazur et al, 2010). Here, KCC2 protein expression was quantified at P11 and P28 following prenatal TSHI using the same protocol of postnatal EPO administration.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been reported that EPO has many unexpected nonhematopoietic functions, including reducing the incidence of bronchopulmonary dysplasia [6], neuroprotection and angiogenesis [7]. Results of studies on injured prenatal brains have shown that neonatal rh-EPO administration is beneficial to myelination [8], rescues neural cells and induces lasting histological and functional improvements [9]. In addition, a retrospective cohort study on premature infants found a dose-response relationship between rh-EPO treatment and improved Mental Developmental Index scores [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although EPO was believed to be produced only in the kidney and liver, Tan and colleagues 28 showed in 1992 that other organs, including the brain, produced this cytokine in response to hypoxic-ischemic stress. This finding paved the way for a plethora of studies that increasingly confirmed a number of interrelated functional roles for EPO in the mammalian brain, some of which form the basis for the studies by Mazur and colleagues 18 reported in this issue of Journal of Neurosurgery: Pediatrics.…”
mentioning
confidence: 80%